Study the Effect of Managers Attitudes on Marketing Strategies and their Related to the Marketing Performance Metrics in Industrial Companies - reza shafei (تحقیقات بازار یابی نوین, 2013)
The research goals are survey of the industrial manager’s attitudes and procedures, the relationship between marketing strategies and markets metrics models. The method was descriptive and the questionnaires were distributed among 85 Tehran food companies’ mangers as well as sales and marketing directors. The findings showed that the managers who use the customer-centric marketing metrics, they applied the metrics that focus to consumers and promotion programs. Also the managers with the market-centric strategies have focused on financial metrics and the competitive-centric strategic managers used innovation related factors. The other results showed that there are significant relationships among the marketing metrics, strategies, and the manager’s views.